1996
DOI: 10.1212/wnl.47.2.603
|View full text |Cite
|
Sign up to set email alerts
|

ApoE epsilon 4 allele and cognitive decline in patients with Alzheimer's disease

Abstract: Many clinical and basic studies have confirmed an association between the apolipoprotein E (apoE) €4 allele and the development of Alzheimer's disease (AD). Corder et al.' reported that survival from onset was unrelated to €4 gene dose. In this issue, Kurz et al.' report that no association of the apoE €4 allele with cognitive decline was found in AD subjects. We examined the relationship between apoE alleles and the rate of cognitive decline in a longitudinal study of up to 3 years.Between February and Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 1 publication
3
20
0
Order By: Relevance
“…The APOE ε4 haplotype is by far the most validated genetic variation and has repeatedly been associated with human longevity (e.g., Asada et al 1996;Bathum et al 2006;Deelen et al 2011;Gerdes et al 2000;McKay et al 2011;Nebel et al 2011;Schachter et al 1994), whereas one study has found association of rs2542052 in APOC3 with longevity (Atzmon et al 2006). The APOE polymorphism was recently reviewed in (Seripa et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The APOE ε4 haplotype is by far the most validated genetic variation and has repeatedly been associated with human longevity (e.g., Asada et al 1996;Bathum et al 2006;Deelen et al 2011;Gerdes et al 2000;McKay et al 2011;Nebel et al 2011;Schachter et al 1994), whereas one study has found association of rs2542052 in APOC3 with longevity (Atzmon et al 2006). The APOE polymorphism was recently reviewed in (Seripa et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…ε4 carriers have been found to demonstrate both slower (4)(5)(6) and faster rates of decline (7)(8)(9)(10)(11)(12)(13), potentially reflecting methodological differences in recruitment techniques, the measurement of cognition, followup time, and participants' stage of dementia. A subset of studies has also demonstrated nondifferential rates of decline in relation to ε4 status (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24); however, most of these studies had relatively small sample sizes which may have limited their ability to detect differential change over time.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Korea did not find a significant difference in the allele frequencies between centenarians and younger controls. Two studies of centenarians in Japan suggest that the 2 allele is associated with lower mortality, but there is no significant association with the 4 allele (11)(12)(13).…”
mentioning
confidence: 99%